The Intervention Analysis of the Interrupted Incidents’ Impacts on Malaysian Tourist Arrivals to Songkhla Province in Thailand - PRAPROM, Chakorn; LAIPAPORN, Jetsada (Journal of Environmental Management and Tourism, 2021)
This study evaluated the impacts of the interrupted incidents on the monthly Malaysian tourist arrivals to Songkhla province in Thailand from January 2004 to December 2019. By applying the Seasonal Autoregressive Integrated Moving Average or SARIMA with intervention model, the estimated coefficients of the most parsimonious model, the SARIMA (1,1,0) (1,0,0) 12 , with intervention model, showed four categories of interrupted incidents that were significantly affected the number of arrivals. These four categories included the insurgency incidents, the political unrests, the natural disasters, and the dieses outbreaks. Most of interrupted incidents significantly decreased the number of arrivals inducing losses in tourism incomes around 370 to 1,031 million baht. However, this study surprisingly found that two insurgency incidents occurring in Narathiwat, a neighbouring province of Songkhla, significantly caused temporary increases in Malaysian tourist arrivals to Songkhla and led to the increase in the tourism income of Songkhla at around 289 million baht. Lastly, based on the estimated model, the forecasts of monthly Malaysian tourist arrivals in 2020 were in the range between 187,633 to 273,929 persons. Then, the forecast of total arrivals to Songkhla in 2020 was approximately 2,471,092 persons or 21.61 percentage increased from the total arrivals in 2019.